2023
DOI: 10.1021/acs.accounts.3c00260
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced C(sp3)–H Functionalization of Glycine Derivatives: Preparation of Unnatural α-Amino Acids and Late-Stage Modification of Peptides

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Peptides are essential components of living systems and contribute to critical biological processes, such as cell proliferation, immune defense, tumor formation, and differentiation. Therefore, peptides have attracted considerable attention as targets for the development of therapeutic products. The incorporation of unnatural amino acid residues into peptides can considerably impact peptide immunogenicity, toxicity, side effects, water solubility, action durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 75 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Notwithstanding these advantages, the direct C­(sp 3 )–H functionalization of glycine or glycine residue in a peptide for the synthesis of unnatural amino acids and site-specific late-stage modification of peptides is still in its infancy . In the past decade, radical-mediated reactions have emerged as mild and efficient approaches to forge unnatural amino acids and peptides via direct C­(sp 3 )–H functionalization of glycine derivatives . These reactions involve either imine ion Int-A via dehydrogenative oxidation or α-carbon radical intermediate Int-B via single-electron oxidation of glycine derivatives followed by deprotonation and 1,2-hydrogen shift (Scheme a).…”
Section: Introductionmentioning
confidence: 94%
“…Notwithstanding these advantages, the direct C­(sp 3 )–H functionalization of glycine or glycine residue in a peptide for the synthesis of unnatural amino acids and site-specific late-stage modification of peptides is still in its infancy . In the past decade, radical-mediated reactions have emerged as mild and efficient approaches to forge unnatural amino acids and peptides via direct C­(sp 3 )–H functionalization of glycine derivatives . These reactions involve either imine ion Int-A via dehydrogenative oxidation or α-carbon radical intermediate Int-B via single-electron oxidation of glycine derivatives followed by deprotonation and 1,2-hydrogen shift (Scheme a).…”
Section: Introductionmentioning
confidence: 94%
“…Various arylated unnatural amino acids and peptides could be synthesized successfully in a green and sustainable manner via this reaction. In contrast with the redox-neutral alkylation mentioned above, the arylation always proceeded via aerobic visible-light-driven oxidation and nucleophilic addition [87][88][89][90][91][92]. In 2012, Rueping et al reported the first application of visible-light photo redox catalysis in the α-C(sp 3 )-H arylation of glycine derivatives and peptides with indoles as the aryl source.…”
Section: α-C(sp 3 )-H Arylationmentioning
confidence: 99%
“…Glycine is the most elementary α-amino acid. Its direct derivatization and modification hold significant relevance in synthesizing unnatural amino acid-containing bioactive peptides and pharmaceuticals. , Past decades have witnessed a booming interest in functionalizing glycine derivatives. Among them, visible light-driven α-C­(sp 3 )–H bond alkylation of glycine derivatives is outstanding as it could deliver diverse alkylated glycine derivatives precisely and efficiently in a green and sustainable manner. Regarding the photocatalysts involved in initiating the reaction, reported visible light-driven approaches toward this objective can be categorized into the following three types (Scheme a): (1) the external photocatalyst (PC) needed visible light-driven C­(sp 3 )–H bond alkylation, in which transition-metal complexes, organic dyes, or quantum dots acted as photocatalysts to absorb visible light and initiate the reaction. (2) photocatalyst-free visible light-driven C­(sp 3 )–H bond alkylation, in which electron donor–acceptor (EDA) complexes always formed and served as internal photocatalysts. (3) visible light-driven C­(sp 3 )–H bond asymmetric alkylation, in which transition-metal asymmetric catalysis and photocatalysis merged to fulfill the synthesis of C­(sp 3 )-alkylated glycine derivatives stereo selectively. The protocols above have demonstrated significant advancements concerning reaction efficiency, selectivity, and the range of applicable substrates. Nevertheless, substantial room exists for further enhancement in various facets of environmentally benign characteristics, including but not limited to catalyst reusability, reaction flexibility, and simplification of postreaction workup procedures.…”
Section: Introductionmentioning
confidence: 99%